2011
DOI: 10.1364/ao.50.002305
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analyzing ghost images for incoherent optical systems

Abstract: In a previous paper [Proc. SPIEPSISDG0277-786X7428, 742807 (2009)10.1117/12.828564], a methodology was developed to model and analyze incoherent ghosts that are formed by two reflections in the paraxial regime. In this paper, we extend the previously developed methodology to model and analyze ghost images that are formed by N (even) reflections. Rather than dealing with ghosts as spots of light, we apply the concept that each ghost has a structure in the nonparaxial regime that depends on the optical system pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Each ghost optical system consists of a specific layout resulting in certain geometric and radiometric properties that are in general different from those of the nominal optical system. In a previous work, a flow chart was introduced to generate the possible ghost layouts from the nominal layout [12][13][14]. For each possible ghost layout, paraxial sequential ray tracing is performed to determine the ghost second-order specifications and the ghost fourth-order aberration function.…”
Section: Ghost Image Analysis Using Geometrical Opticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each ghost optical system consists of a specific layout resulting in certain geometric and radiometric properties that are in general different from those of the nominal optical system. In a previous work, a flow chart was introduced to generate the possible ghost layouts from the nominal layout [12][13][14]. For each possible ghost layout, paraxial sequential ray tracing is performed to determine the ghost second-order specifications and the ghost fourth-order aberration function.…”
Section: Ghost Image Analysis Using Geometrical Opticsmentioning
confidence: 99%
“…The ghost depth of focus can become a useful design tool when considering a system that is normally prone to ghosts. In the nonparaxial regime, off-axis ghosts may be focused at the nominal image plane if there is an intersection between the sagittal/ tangential ghost image surface and the nominal image plane [12].…”
Section: Ghost Image Analysis Using Geometrical Opticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the ARP in the Focal Plane Assembly (FPA) and the filters give rise to a common problem with visible cameras, that is the formation of ghost images; ghosts are created by the reflection of the beam inside the filters/ARP or by multiple reflections from the detector, filter and ARP surfaces [12] [13]. These ghosts are evident in an image as attenuated and defocused halos generally displaced or overlapped to the original features.…”
Section: Filters and Focal Plane Assemblymentioning
confidence: 99%
“…Several authors have showed that most inhibitors were adsorbed onto the metal surface by displacing water molecules from the surface and forming a compact barrier film [13,32,33]. Perusal of literature reveals that many N-heterocyclic compounds such as pyrimidine derivatives [14], triazole derivatives [15], tetrazole derivatives [16], phenyltetrazole derivatives [17,18], indole derivatives [19], pyridazine derivatives [20], and benzimidazole derivatives [21], to mention but a few, have been used for the corrosion inhibition of iron or steel in acidic media. The effectiveness of quinoxaline derivatives (N-heterocyclic compounds) as effective corrosion inhibitors for carbon steel in acid media has been reported [22][23][24].…”
Section: Introductionmentioning
confidence: 99%